Case Report: Effect of transcutaneous auricular vagus nerve stimulation on acute pain after external fixation for bilateral open tibiofibular fractures - Li, Qi; Zhao, Donglin; Zhang, Shuyang; Du, Xinyu; Ding, Ning; Xing, Zheng; Chu, Xiaolei; Xu, Weiguo (Frontiers in Neuroscience, 2025)
A 50-year-old female patient sustained bilateral tibiofibular fractures due to a traffic accident and underwent open external fixation surgery on both lower limbs. Postoperatively, she reported severe pain (VAS ≥ 8). The patient had no significant underlying medical conditions or contraindications to vagal nerve stimulation. Transcutaneous auricular vagus nerve stimulation (taVNS)—a non-invasive modality that activates vagal pathways to modulate sympathetic-parasympathetic balance, suppress inflammation, and inhibit pain signaling—was trialed as an adjunctive analgesic intervention. Heart rate variability (HRV) was incorporated as an objective biomarker to quantify dynamic changes in autonomic function and their association with pain relief. After stabilization, taVNS was administered continuously for two weeks. Parameters monitored included immediate pressure pain thresholds (PPT) during intervention, daily postoperative analgesic consumption, and pre-/post-intervention Visual Analog Scale (VAS) and Generalized Anxiety Disorder-7 (GAD-7) scores. Dynamic electrocardiography was used to record HRV parameters (HR, SDNN, RMSSD, LF, HF, LF/HF). Post-intervention, the patient demonstrated significant reductions in VAS scores, a progressive increase in PPT, and alleviated anxiety. HRV analysis revealed enhanced parasympathetic activity and improved sympathovagal balance. This case suggests that taVNS may effectively alleviate acute postoperative pain by modulating autonomic function. Dynamic HRV monitoring provided objective evidence of pain-autonomic nervous system interactions, supporting taVNS as a complementary strategy for postoperative pain management. However, as a single-case report, this study has limited sample size, necessitating further large-scale randomized controlled trials to validate these findings.